Effectiveness of Yoga Movements in Reducing the Pain of Dysmenorrhea in Adolescent Women in SMAN 1 Tambang - Nia Desriva; Ary Oktora Sri Rahayu; Tukimin (Universitas STRADA Indonesia, 2022)
Menstrual pain or dysmenorrhea is defined as pain that occurs before or during a menstrual period, this pain may last from one to several days. Dysmenorrhea is menstrual pain that is often complained of by women, which is characterized by brief pain before or during menstruation (Lowdermilk et al., 2011). There are many ways to reduce dysmenorrhea pain, one of which is yoga. Yoga helps the body's endocrine glands function better, and when done for at least 30 seconds during your period, it can help relieve dysmenorrhea and facilitate menstruation. The purpose of this study was to analyze the effectiveness of yoga movements in reducing dysmenorrhea pain.The research design was pre-experimental designs, using one group pre-test and post-test. Samples are taken by technique purposive samplings many as 24 respondents. Data were analyzed univariately and bivariately using the Wilcoxon Signed Rank test. Univariate results before doing yoga results obtained most of the students experienced pain on average on a scale of 4, namely 11 respondents (45%) and on a pain scale of 3, namely 7 female students (29%). female students (62%). The bivariate results obtained that there was an effect of yoga movement on dysmenorrhea pain in young women at SMAN 1 Tambang with a p value of 0.000. It was concluded that there is effectiveness of yoga movements in relieving dysmenorrhea pain and there are significant differences between before and after doing yoga movements. It is recommended that young women do yoga regularly to relieve dysmenorrhea pain.